PENINGKATAN MOTIVASI KEWIRAUSAHAAN WARGA DESA CIAMPEA UDIK MELALUI PELATIHAN BUCKET - Qurratul Ain Arifah Batubara; Sifha Hafiza; Edi Sutoyo; Fitriani Fitriani; Gatot Eka Pramono (Lembaga Penelitian dan Pengabdian kepada Masyarakat UIKA Bogor, 2025)
Entrepreneurship training teaches how to become an independent business owner and create and maintain a business environment by prioritizing entrepreneurial traits and behaviors, such as being innovative, accepting risks, taking responsibility, and respecting diversity. The bucket-building entrepreneurship training held by group 22 in the thematic KKN program in 2023 at the University of Ibn Khaldun Bogor, apart from aiming to provide provisions for Ciampea Udik villagers, also intends to encourage entrepreneurial motivation. The effect of training on the entrepreneurial basis of residents was studied through data collection by filling out a questionnaire after the training. The results showed that almost all participants stated that the bucket training activities benefited them. Many of the participants wanted to start entrepreneurship by using social media, and some were interested in trying entrepreneurship after they graduated from school. From the activities carried out, it can be concluded that entrepreneurship training activities make bucket very influential on the participants' motivation in entrepreneurship.